2004
DOI: 10.1007/s00299-004-0774-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin-induced abnormal shoot organogenesis is associated with elevated Knotted1-type homeobox gene expression in tobacco

Abstract: The molecular mechanisms that regulate the transcription of key developmental genes involved in shoot organogenesis have yet to be fully elucidated. However, it is clear that plant growth regulators, such as cytokinin, play a critical role in the differentiation of adventitious shoots. In Nicotiana tabacum zz100 leaf discs, high frequency shoot formation could be induced with 5 microM of the cytokinin N6-benzyladenine (BA). Increasing the exogenous BA concentration to greater than 20 microM resulted in stunted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…In other words, this type of acute defect is a terminal one because the regenerant will not complete a life cycle. Impaired in vitro organogenesis has been attributed to detrimental influences of PGRs, and a pivotal role for cytokinins specifically in the differentiation of normal or abnormal shoot meristems has been suggested (Toponyanon et al, 1999;Howell et al, 2003;Ramage and Williams, 2004). We show here for the first time that stemdeficiency appears also in cultures not treated with PGRs (Table 1).…”
Section: Discussionsupporting
confidence: 43%
“…In other words, this type of acute defect is a terminal one because the regenerant will not complete a life cycle. Impaired in vitro organogenesis has been attributed to detrimental influences of PGRs, and a pivotal role for cytokinins specifically in the differentiation of normal or abnormal shoot meristems has been suggested (Toponyanon et al, 1999;Howell et al, 2003;Ramage and Williams, 2004). We show here for the first time that stemdeficiency appears also in cultures not treated with PGRs (Table 1).…”
Section: Discussionsupporting
confidence: 43%
“…Previously, it has been reported that elevated levels of exogenous cytokinin could lead to the initiation of abnormal shoots (Ramage and Williams 2004). In this study, the presence of various cytokinins lead to abnormal morphology of regenerated shoots.…”
Section: Discussionmentioning
confidence: 96%
“…Plant regeneration through organogenesis induced abnormal morphology in Nicotiana tabaccum and Camellia sinensis (Mondal et al 2004;Ramage and Williams 2004). In earlier reports, indirect organogenesis of H. dulcis resulted in abnormal morphology when shoots are grown on MS medium supplemented with GA 3 and kinetin (Park et al 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Through its interaction with auxin, cytokinin is involved in adventitious root and shoot formation (Miller et al, 1955), leaf senescence, vascular development, and lateral bud formation (Mok and Mok, 1994). The determination times associated with the process of shoot or root differentiation and related phenomena have been investigated by pretreating tissues with auxin and cytokinin, then transferring them to hormone-free media (Ramage and Williams, 2004;Christianson and Warnick, 1983). This 'time', defined as when organ formation is observed in plant segments, can differ among individuals within the same species (Ramage and Williams, 2004).…”
mentioning
confidence: 99%
“…The determination times associated with the process of shoot or root differentiation and related phenomena have been investigated by pretreating tissues with auxin and cytokinin, then transferring them to hormone-free media (Ramage and Williams, 2004;Christianson and Warnick, 1983). This 'time', defined as when organ formation is observed in plant segments, can differ among individuals within the same species (Ramage and Williams, 2004). In addition, no plant growth-regulating substance is needed after that determination occurs (Komamine et al, 1992).…”
mentioning
confidence: 99%